Building regression models with SAS : a guide for data scientists - Rodriguez, Robert N. (SAS Institute, 2023)
Building Regression Models with SAS: A Guide for Data Scientists teaches data scientists, statisticians, and other analysts who use SAS to train regression models for prediction with large, complex data. Each chapter focuses on a particular model and includes a high-level overview, followed by basic concepts, essential syntax, and examples using new procedures in both SAS/STAT and SAS Viya. Building Regression Models with SAS is an essential guide to learning about a variety of models that provide interpretability as well as predictive performance.